The Subterranean Chamber of the Pyramid of Khufu: A Ritual Map of Ancient Egypt? - Nelson, Roger D. (Journal of Scientific Exploration, 2025)
Careful examination of the ‘Pit’ in the Great Pyramid of Khufu on the Giza plateau reveals that this subterranean chamber is not unfinished or abandoned as has been suggested by many observers. The walls and ceiling are smooth, and the floor, which at a glance looks rough and unstructured, actually is carved into a very pronounced and certainly meaningful form. A survey of the historical literature shows that only a few scholars, primarily those interested in esoteric material, have regarded the underground room as important and potentially revealing. Based on this literature and on direct observation, a speculative interpretation is developed to suggest that the sculpted floor may be a symbolic map of the Egyptian world of 4500 years ago. A FieldREG recording of the sort that is often correlated with anomalous effects of consciousness displays a significant response in this chamber, adding to the factors that should stimulate an incisive, expert assessment of the subterranean chamber and its probable function for the ancient Egyptians who built it.